(untitled) (Res Gesta, 2020)
On December 29, 2019, the Facultad de Derecho y Ciencias Sociales del Rosario celebrated its 60th anniversary. It was founded at the end of 1959 with the support of Monsignor Antonio Caggiano, and on the initiative of some well-known lawyers from Rosario -among them, the outstanding jurist and first dean, Dr. Juan Casiello-, the School was integrated to the Argentine Catholic University, which had been built a year before in the city of Buenos Aires. Its courses were officially inaugurated in March 1960, responding at the same time to the aspiration of the Catholic sectors to have their own institutions of higher education, and to the demand of the local society for the creation of a School of Law in the city.